1996
DOI: 10.1200/jco.1996.14.8.2295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of external immunoscintigraphy with the IMMU-4 technetium-99m Fab' antibody fragment in patients undergoing surgery for carcinoma of the colon and rectum: results of a pivotal, phase III trial. The Immunomedics Study Group.

Abstract: CEA-Scan affords high-quality, same-day imaging, uses an inexpensive and readily available radio-nuclide, adds clinically significant information in assessing extent and location of disease in colorectal cancer patients, and only rarely induces a HAMA response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(47 citation statements)
references
References 14 publications
1
45
0
1
Order By: Relevance
“…The panel does not recommend the use of anti-CEA--radiolabeled scintigraphy. 252 In the event that surgically curable metastatic disease is identified on CT or MRI, the panel does recommend a PET scan before surgical resection to look for evidence of additional metastases that may change the status of patient resectability.…”
Section: Managing An Increasing Carcinoembryonic Antigen Levelmentioning
confidence: 99%
“…The panel does not recommend the use of anti-CEA--radiolabeled scintigraphy. 252 In the event that surgically curable metastatic disease is identified on CT or MRI, the panel does recommend a PET scan before surgical resection to look for evidence of additional metastases that may change the status of patient resectability.…”
Section: Managing An Increasing Carcinoembryonic Antigen Levelmentioning
confidence: 99%
“…By using this Raman-modified endoscope, Shim et al (383) demonstrated that Raman spectra of human gastrointestinal tissues could be obtained with acceptable signal-to-noise ratio and good temporal resolution. Moreover, through the use of diagnostic algorithms for classifying colon polyps based on their spectral characteristics, adenomatous polyps could be differentiated from hyperplastic polyps with great accuracy (296,383).…”
Section: Raman Imagingmentioning
confidence: 99%
“…(48). Hepatic uptake of this agent hindered interpretation of possible metastases in the liver, but a 99m Tc-labeled anti -carcinoembryonic antigen (CEA) FabV fragment improved the visualization of tumors in the liver (49). Currently, [ 18 F]deoxyglucose, with the improved sensitivity afforded by positron emission tomography imaging systems, has become the standard for oncology radionuclide imaging.…”
Section: Pretargeting For Improved Imagingmentioning
confidence: 99%